S110 Concise whole blood transcriptional signatures for incipient tuberculosis: a systematic review and individual participant data meta-analysis. (12th November 2019) - Gupta, RK; Turner, CT; Venturini, C; Esmail, H; Rangaka, MX; Copas, A; Lipman, M; Abubakar, I; Noursadeghi, M
Abstract : Background: Blood transcriptional signatures may predict risk of tuberculosis (TB). While multiple candidate signatures for active and incipient TB have been identified, it is not known which signature performs best, or whether any meets World Health Organization target product profile (WHO TPP) benchmarks, for incipient TB biomarkers. Methods: We performed a systematic review to identify candidate mRNA signatures for incipient TB, along with genome-wide transcriptomic datasets with sampling prior to TB diagnosis. We reconstructed each signature model and directly compared signature performance for diagnosis of incipient TB in the pooled RNAseq dataset, stratified by interval to disease, in a one-stage individual participant data meta-analysis (IPD-MA). Results: We tested 17 candidate mRNA signatures in a pooled dataset from four studies conducted in South Africa, Ethiopia, The Gambia and the UK. We included 1, 126 samples, with 183 samples from 127 incipient TB cases, Eight signatures (comprising 1–25 transcripts), predominantly reflecting interferon-inducible gene expression, had equivalent diagnostic accuracy for incipient TB over a two-year period with areas under the receiver operating characteristic curves ranging from 0.70 (95% confidence interval 0.64–0.76) to 0.77 (0.71–0.82). The sensitivity of all eight signatures declined with increasing disease-free time interval. Using a threshold derived from two standard deviations above the mean of uninfected controls, giving specificities of >90%, the eight signatures achieved sensitivities of 24.7–39.9% over 24 months, rising to 47.1–81.0% over 3 months. Based on pre-test probability of 2%, the eight signatures achieved positive predictive values from 6.8–9.4% over 24 months, rising to 11.1–14.3% over 3 months. When using biomarker thresholds maximising sensitivity and specificity with equal weighting to both, no signature met the minimum WHO TPP parameters for incipient TB biomarkers over a two-year period. Sensitivity analyses using two-stage IPD-MA with random effects produced similar AUC, sensitivity and specificity estimates. Conclusions: Multiple transcriptional signatures perform with equivalent diagnostic accuracy for incipient TB. These biomarkers reflect short-term risk of TB and only exceed WHO benchmarks if applied to 3–6 month intervals. A screening strategy that incorporates serial testing on a 3–6 monthly basis among carefully selected target groups may be required for optimal implementation of these biomarkers.